(untitled) (Eurasian Journal of Philology Science and Education, 2016)
This article discusses the weaknesses requiring the investigation of the theme of the novel «Akbilek» by Jusipbek Aimauytov who was an influential person in the development of literature in the early twentieth century, despite the fact, the truth of the historical era, methods and skills in the writer’s artistic speech, style personality of this novel, which is a prominent work of art in a prose genre are being researched comprehensively. In the early twentieth century actual literary issues which were noticed by writers from the viewpoint of directions of the artistic development of Kazakh literature, creative interaction, the truth of historical era in fiction literature, the writer’s skills to grow up image of the characters; the use of language in understanding and evaluating; writing a portrait of the dynamics of action, etc. there are quite a lot of phenomena to study in a creative talent and personality of Jusipbek Aimauytov.